An Assessment of the Vulnerability of Tehran’s Farahzad District in A Possible Earthquake - Seyedeh Faezeh Mirhosseini; Akbar Haj Ebrahim Zargar; Sharif Motavef (صفه, 2020)
Tehran has always been vulnerable to possible earthquakes, with informal settlements being most at risk and their worn-out urban context exacerbated by socio-economic problems. Studied here, is the Farahzad neighbourhood, one of the informal settlements in Tehran, which is extremely vulnerable to earthquakes.‎ The purpose of this study is to investigate the extent of the vulnerability in this neighbourhood by using scenario planning for possible damages and casualties. The research method is descriptive-‎analytical with a quantitative approach. The spatial analysis is conducted using Arcmap software, and data collection methods include the study of documents along with exploratory interviews with residents.‎ After recognising the neighbourhood and studying its vulnerabilities using the models suggested for a possible earthquake in Tehran, the worst-case scenario is considered, namely, an earthquake caused by the fault in northern Tehran. Working out the extent of vulnerability and the degree of destruction of buildings, infrastructures, and other aspects of damages, it is concluded that the Farahzad neighbourhood would face a 65% damage to its built environment, meaning between 1153 and 1345 buildings will be damaged seriously, and human casualties would reach more than 500 people if the quake occurs at night.‎